Japan : Recent Economic Developments. (IMF Staff Country Reports; Country Report ;, 1996)
This paper reviews economic developments in Japan during 1994. It focuses on the weak recovery that began in 1994, and the subsequent strengthening of growth since mid-1995. The paper examines developments in output and prices, and reviews the role that fiscal policy has played in providing support to demand, and the resulting sharp deterioration in the fiscal position. Monetary developments, including the reduction in interest rates to record lows in 1995, are discussed. The paper analyzes developments in the external sector and exchange markets. Developments in trade and structural policies are also reviewed.